2010
DOI: 10.1098/rsta.2010.0089
|View full text |Cite
|
Sign up to set email alerts
|

Quantum oscillations probe the normal electronic states of novel superconductors

Abstract: In 2008, new classes of high-temperature superconductors containing iron have been discovered. These iron pnictides offer a new area of exploration and understanding of superconductivity. Quantum oscillations is a bulk probe that allows us to map out the full Fermi surface of a superconducting system in its normal metallic state. These oscillations are determined by the Landau quantization in high magnetic fields and are usually observed at very low temperatures and in very clean samples. By knowing the exact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…The main studies of the multiple-orbital models which have been carried out for the heavy-fermion and Fe-based materials have been based upon weak-coupling RPA (Kuroki et al, 2008Graser et al, 2009;Chubukov, 2012), FLEX (Ikeda, Arita, and Kuneš, 2010), or FRG methods (Platt, Honerkamp, and Hanke, 2009;Wang, Wan, and Wang, 2009;Zhai, Wang, and Lee, 2009;Uebelacker and Honerkamp, 2012). Just as the Monte Carlo calculations (Maier, Jarrell, and Scalapino, 2006b) of the four-point vertex allow one to study the interplay of the various spin, charge, and pairing correlations on an equal footing as the temperature is reduced (see, for example, Fig.…”
Section: Multiorbital Modelsmentioning
confidence: 99%
“…The main studies of the multiple-orbital models which have been carried out for the heavy-fermion and Fe-based materials have been based upon weak-coupling RPA (Kuroki et al, 2008Graser et al, 2009;Chubukov, 2012), FLEX (Ikeda, Arita, and Kuneš, 2010), or FRG methods (Platt, Honerkamp, and Hanke, 2009;Wang, Wan, and Wang, 2009;Zhai, Wang, and Lee, 2009;Uebelacker and Honerkamp, 2012). Just as the Monte Carlo calculations (Maier, Jarrell, and Scalapino, 2006b) of the four-point vertex allow one to study the interplay of the various spin, charge, and pairing correlations on an equal footing as the temperature is reduced (see, for example, Fig.…”
Section: Multiorbital Modelsmentioning
confidence: 99%
“…We recall that the hybridization in 122 compounds can be traced to the checkerboard arrangement of pnictogen/chalcogene atoms staggered above and below the iron planes, [57][58][59][60] . The iron lattice sites at iax+jaŷ +kcẑ, with integer i, j, k then belong to even and odd sublattices, defined by an even and odd i + j + k, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of a spinorbit interaction λ k does not have zeros even in 1111 systems 13,14 . Because our goal is to understand the generic effect of the hybridization between the two bands, we will treat λ k as a constant λ 14,16 . Earlier analysis of the effect of λ k including its angular dependence (but without interplay with inter-pocket pairing) has shown that the results are qualitatively the same as for constant λ 10 .…”
Section: The Modelmentioning
confidence: 99%